2015
DOI: 10.4103/0366-6999.168989
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Encephalitis Associated with Anti-γ-aminobutyric Acid B Receptor Antibodies

Abstract: Background:Autoimmune encephalitis associated with antibodies against γ-aminobutyric acid B receptor (GABAB R) in patients with limbic encephalitis (LE) was first described in 2010. We present a series of Han Chinese patients for further clinical refinement.Methods:Serum and cerebrospinal fluid (CSF) samples from patients referred to the program of encephalitis and paraneoplastic syndrome of Peking Union Medical College Hospital were tested with indirect immunofluorescence. Clinical information of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
54
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 16 publications
12
54
3
Order By: Relevance
“…Our study showed that memory deficit is common in these patients and that complete recovery is difficult, which may be closely related to damage to the marginal lobe. Psychiatric disorders are common (64.7%) [7] in patients with anti-GABABR encephalitis, and this result is roughly in line with our finding. Mental disorders are also common symptoms that tend to persist until the patient is discharged.…”
Section: Clinical Manifestationssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that memory deficit is common in these patients and that complete recovery is difficult, which may be closely related to damage to the marginal lobe. Psychiatric disorders are common (64.7%) [7] in patients with anti-GABABR encephalitis, and this result is roughly in line with our finding. Mental disorders are also common symptoms that tend to persist until the patient is discharged.…”
Section: Clinical Manifestationssupporting
confidence: 92%
“…Epilepsy is a prominent and critical clinical manifestation of anti-GABABR encephalitis, and epilepsy or refractory epilepsy is often the first symptom [6]. In a previous study by Guan et al, 17 of the 18 patients presented with new refractory epilepsy or status epilepticus [7], while all the patients in our study had epilepsy. Herpes simplex encephalitis is perhaps most frequently associated with epilepsy, of the types of sporadic viral encephalitis, with an incidence of about 50% in cases of combined epilepsy [8].…”
Section: Clinical Manifestationsmentioning
confidence: 41%
“…To the best of our knowledge, there were 48 cases [5][6][7] reported in China, and the average age was about 56 years old, which was smaller than that reported in 2010 (62 years) [2]. And most of them were middle-aged and old men (about 65%).…”
Section: Descriptionmentioning
confidence: 95%
“…It has been reported that patients with SCLC might have unfavorable treatment outcomes if using the immunotherapy. And the main causes of death in patients with anti-GABA B R encephalitis were lung tumor progression and chemotherapy related complications [2,6,10]. Therefore, it is necessary to attach great importance to the detection of tumor or paraneoplastic biomarkers.…”
Section: Descriptionmentioning
confidence: 99%
“…Surprisingly, despite the prominent psychiatric symptoms and the importance of psychiatric involvement in its treatment, the psychiatric literature on the disease is relatively scarce [5,6]. Even more surprisingly, there are few reports on anti-NMDAR encephalitis from the perspective of psychiatrists in China [11,12,13]. It is largely unknown whether there are differences in psychiatric symptoms between patients with anti-NMDAR encephalitis who initially present with psychiatric symptoms and new-onset psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%